Barriers to Using Mobile Devices in the Classroom - Angela Triplett; William J. Triplett (Gemilang Maju Publikasi Ilmiah (GMPI), 2023)
Mobile devices in specific, cell phones have become progressively trendy. Even though the usage of mobile devices can accelerate the learning process, there may be obstacles to utilizing it for learning purposes. This study directed to recognize and examine the barriers and catalysts of using mobile devices as an educational device from the perspective of educators. The numerous barriers impeding the effective integration of mobile devices in the classroom have been identified. This study has uncovered several key findings that shed light on the challenges hindering the effective integration of mobile devices in the classroom.